Increasing Knowledge, Attitudes, and Behavior on Disaster Preparedness Through Disaster Literacy Counseling for Students of SDN Kaliwungu, Kudus Regency - Muhammad Navis Mirza (PT FORMOSA CENDEKIA GLOBAL, 2023)
Disasters that occur apart from natural factors are also caused by human activities. Almost all activities carried out by humans will have an impact on environmental damage and in turn have an impact on humans themselves in Kudus Regency, in 2019 there were 28 floods, 9 landslides and 167 fires, although only 2 schools were affected. For this reason, knowledge is needed for students who are agents of the future to be able to reduce activities that can cause damage to nature. The school literacy movement is expected to spur the formation of a mindset by inserting disaster literacy material including reading books, discussions and simulations. The purpose of this study was to determine the effect of disaster literacy education on increasing knowledge, attitudes and behavior